Immobilization of laccase from Pleurotus ostreatus on magnetic separable SiO2 support and excellent activity towards azo dye decolorization. Issue 2 (June 2016) - Dai, Jianan; Wang, Hongxia; Chi, Hui; Wang, Yingying; Zhao, Jingxiang
Abstract: In present study, laccase from Pleurotus ostreatus, was immobilized on Fe3 O4 /SiO2 nanoparticles by using glutaraldehyde as coupling agent. It was the first time to immobilize laccase from Pleurotus ostreatus on nonporous Fe3 O4 /SiO2 nanoparticles at the nanoscale. Not only rapid color removal of phenolic azo dye in one hour was realized, but also unusual operational stability and storage stability of the immobilized laccase from Pleurotus ostreatus were detected. The residue activity of the immobilized laccase that has been stored for 5 months at 4 °C almost keeps the enzyme activity of the fresh-prepared immobilized laccase when Procion Red MX-5B was used as substrate, the decolorization percentage in one hour was still 96%, better than all those reported previously. Therefore, the excellent performance of the immobilized laccase with nonporous Fe3 O4 /SiO2 nanoparticles as support might have more promising potentials for laccase in the treatment to the dye-containing wastewater.